Validation of the preliminary criteria for the classification of catastrophic antiphospholipid syndrome. Issue 8 (11th February 2005) - Cervera, R; Font, J; Gómez-Puerta, J A; Espinosa, G; Cucho, M; Bucciarelli, S; Ramos-Casals, M; Ingelmo, M; Piette, J-C; Shoenfeld, Y; Asherson, R A
Abstract : Objective: To describe the characteristics of patients with catastrophic antiphospholipid syndrome (APS) included in the International Registry of patients with this condition (CAPS registry) and to analyse the value of the recently proposed preliminary criteria for the classification of catastrophic APS. Methods: A review of the first 220 patients included in the website based CAPS registry was undertaken and the preliminary criteria for their classification were tested; 175 unselected patients with systemic lupus erythematosus or APS, or both, acted as controls. Results: The mean age of the patients was 38 (14) years (range 7 to 74), with a female preponderance (F/M, 153/67). The main clinical manifestations included renal involvement in 154 (70%), pulmonary in 146 (66%), cerebral in 133 (60%), cardiac in 115 (52%), and cutaneous in 104 (47%); 114 patients (52%) recovered after the catastrophic APS event (mortality 48%). Patients who received the combination of anticoagulation plus steroids plus plasma exchange or intravenous immunoglobulins had the best survival rate (63%, p = 0.09). Sufficient data could be analysed for application of the classification criteria in 176 patients. According to the preliminary criteria, 89 patients (51%) could be classified as having "definite" and 70 (40%) as having "probable" catastrophic APS, thus given a sensitivity of 90.3% with a specificity of 99.4%. Positive and negative predictive values were 99.4% and 91.1%, respectively. Conclusions: The preliminary criteria for the classification of catastrophic APS and the CAPS registry are useful tools for epidemiological studies.